The Relationship of Mother's Nutritional Knowledge and Feeding Patterns with Events Stunting in Toddler Ages 12-59 Months In the Working Area of Sijunjung Health Center - Irwadi; Andre Utama Saputra; Yenni Elﬁra (MultiTech Publisher, 2023)
Indonesia is the third country with the highest prevalence in Southeast Asia with the number of stunting at 30.8% above the limit set by WHO, namely 20%. West Sumatra Province in 2021 the incidence of stunting was 25.6%. One area with a proportion of stunted toddlers is Sijunjung at 30.1%. The aim of this research is to determine the relationship between maternal knowledge about nutrition and feeding patterns and the incidence of stunting in toddlers aged 12-59 months in the Sijunjung health center working area. This research is a descriptive study with an analytical survey, and the design is cross sectional. The population of this study were all mothers with children under five who were in the working area of ​​the Sijunjung Community Health Center. Purposive sampling was used to select 30 mothers and toddlers aged 12-59 months. This research uses a questionnaire as a research instrument. The research results show that there is a relationship between maternal nutritional knowledge and stunting with a p-value of 0.005 > 0.05, and there is a relationship between feeding patterns and stunting with a p-value of 0.001 > 0.05. And to the community health center.